Mobility for learners and staff – higher education students and staff mobility inter-institutional agreement 2013-2016 between programme countries - Bauhaus-Universität Weimar and Universidade Lusíada de Lisboa - Universidade Lusíada de Lisboa (2015)
- Cooperate in the activities within SOCRATES II programme. - Subject area: Architecture, Urban and Regional Planning.